PEMBERDAYAAN GENERASI MILENIAL MELALUI KERAJIANAN TANGAN MERAJUT UNTUK MENINGKATKAN PENDAPATAN PADA MASA PANDEMI COVID 19 - Tasya Arbayani; Haidir Lubis; Qorisya Fahzira (Cattleya Darmaya Fortuna, 2022)
The COVID-19 pandemic has had an impact on all fields, including the family economy. The purpose of service activities is to carry out a community assistance process to recognize and make knitting skills, and produce products that can be marketed to improve the economy of the community. This service activity is carried out in three ways, namely training, implementation and mentoring. The subject of this service activity is the Youth of Kotangan Village, Galang District, Kab. Deli Serdang. The results of this activity include two things, first, the partner community has increased in terms of knowledge, understanding and skills in and the achievement of increased partner skills in the form of knitted bag models, cap models, mask connector models, as well as hats and skullcaps. Second, the products that have been produced have begun to be marketed through online media in Deli Serdang Regency. The achievement of this service activity is very dependent on the consistency of the partner's spirit to work during this pandemic.